BENTUK LEMBAGA YANG IDEAL DALAM PENGELOLAAN SAMPAH DI DAERAH (STUDI DI KOTA MALANG DAN KABUPATEN GIANYAR) - Qodriyatun, Sri Nurhayati (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2015)
Waste is common problem faced by many cities in Indonesia, but not all cities have provided a good waste services. One of the factors that affect the low level waste services in a city is a form of waste management agency or institution. In general, the capacity or the ability of the waste service institutions in many cities are smaller than the amount of waste that should they manage. The research has been done in 2013, by using qualitative methods. It is concluded that the institution of waste management needs to be split between the regulator and the operator. Dinas works as regulator and BLUD as operator. The separation of role on institution of the waste management will lead the institution’s work getting more effective and efficient.